Beyond inflammation: the multifaceted therapeutic potential of targeting the CXCL8-CXCR1/2 axis in type 1 diabetes - Fousteri, Georgia; Jones, Meghan; Novelli, Rubina; Boccella, Serena; Brandolini, Laura; Aramini, Andrea; Pozzilli, Paolo; Allegretti, Marcello (Frontiers in Immunology, 2025)
Identifying novel therapeutic targets involved in the multiple mechanisms underlying the complex pathophysiology of type 1 diabetes (T1D) could change the natural history of this disease. The CXCL8-CXCR1/2 axis is emerging as a therapeutic target with a crucial, multifaceted role in T1D pathophysiology. CXCL8-dependent neutrophil chemotaxis to the pancreas precedes autoimmunity, and CXCR1/2 blockade mitigates insulitis and T1D development in preclinical models. In parallel, CXCL8 can act in a β cell-autonomous manner, and exert non-immune actions on adipocytes, hepatocytes, podocytes, and muscle cells that contribute to insulin resistance and diabetic complications. In this review, we delineate compelling evidence of immune and non-immune actions of the axis in the onset and progression of T1D. We show that the CXCL8-CXCR1/2 axis represents a promising therapeutic target for the prevention/reversal of T1D, with a meaningful potential clinical advantage conveyed by its role in multiple components of the pathology and diabetic complications.